Non observance of gricean maxims in the occurrences of evasion during THE Malaysian parliamentary question time / Nur Najah Radhiah Zainal Abidin - Nur Najah Radhiah , Zainal Abidin (2023)
Until recently, research on evasion has been predominantly conducted in the context of political interviews and lacked focus on parliamentary discourse (Rasiah, 2007; Bull & Mayer, 2020). Further, exploring the contextualization of the Cooperative Principle (CP) and its conversational maxims by activity types, as discussed by Mooney (2004), in the parliamentary context should also be considered. This is because previous studies have shown how institutional norms and constraints can influence the CP (e.g., Antaki & Stokoe, 2017). This qualitative study utilizes Grice’s (1975) Framework of Conversational Maxims, Harris’ (1991) Framework of Responses, and Clayman’s (2001) Framework of Evasion to analyze 360 question and response pairs from pre- and post- Malaysian 14 General Election hansards. While the study primarily focused on the nonobservance of maxims in evasions, it also examined the non-observance of maxims in direct and indirect answers to explore their differences. The study uncovered that MPs commonly resorted to evasive responses during parliamentary question-and-answer sessions, with medium-level evasive responses being the most prevalent, followed by full evasive responses. Ministers and deputy ministers from both governments also frequently utilized overt strategies by declining to answer questions and providing reasons for their shift in focus. The study's findings demonstrate that evasive responses may be considered cooperative if both the questioner and responder engage in an adversarial exchange. Nevertheless, the study also recognizes that the conversation's "common purpose" changes when questioners pursue evaded questions, emphasizing the significance of acknowledging institutional norms and practices in shaping interpretations of cooperative behavior and developing effective communication strategies that consider these norms and practices. The study's implications have several crucial considerations for understanding communication dynamics in parliamentary question-and-answer sessions. Firstly, it highlights the importance of recognizing institutional norms and practices' role in shaping the interpretation of cooperative behavior as discussed in Grice (1975, 1989) and developing effective communication strategies that account for them. Secondly, the study challenges the existing evasion framework proposed by Clayman (2001), suggesting a need to restructure the framework to incorporate differences in evasive strategies used in various communication contexts. Finally, the study stresses the importance of a nuanced analysis of linguistic strategies employed in each context, taking into account their relation to broader communication goals and objectives. These implications underscore the intricate nature of communication dynamics and the necessity of developing effective communication strategies that consider the nuances of distinct communication contexts and constraints.